2016
DOI: 10.1007/s10552-016-0728-3
|View full text |Cite
|
Sign up to set email alerts
|

History of uterine leiomyoma and risk of endometrial cancer in black women

Abstract: Background Previous studies have found an association between uterine leiomyomata (UL) and uterine malignancies. This relation has not been studied in black women, who are disproportionately affected by UL. Methods We investigated prospectively the association between self-reported physician-diagnosed UL and endometrial cancer in the Black Women’s Health Study. During 1995–2013, 47,267 participants with intact uteri completed biennial health questionnaires. Reports of endometrial cancer were confirmed by pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…This is because up to 50% of women with uterine fibroids have no clinical symptoms [4,7] and the prevalence of uterine fibroids is higher in the general population when pelvic examination and ultrasound are included (reviewed in [6]). Importantly, in Wise's, Fortuny's or Brinton's study [16][17][18], the prevalence of uterine fibroids in controls was 37% in black women, 20% in white women, and 2.2% in Danes (Table 4). The prevalence of uterine fibroids reported in those studies were significantly lower than what other studies reported in the literature, where the estimated cumulative incidence of uterine fibroids by age 50 years was 80% for black women and 70% for white women [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because up to 50% of women with uterine fibroids have no clinical symptoms [4,7] and the prevalence of uterine fibroids is higher in the general population when pelvic examination and ultrasound are included (reviewed in [6]). Importantly, in Wise's, Fortuny's or Brinton's study [16][17][18], the prevalence of uterine fibroids in controls was 37% in black women, 20% in white women, and 2.2% in Danes (Table 4). The prevalence of uterine fibroids reported in those studies were significantly lower than what other studies reported in the literature, where the estimated cumulative incidence of uterine fibroids by age 50 years was 80% for black women and 70% for white women [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that uterine fibroids shares common pathogenesis, some clinical characteristics and pathological parameters with endometrial cancer. Few studies reported that uterine fibroids increased the risk of developing both endometrial and ovarian cancers [16][17][18][19][20]. However, another study reported that uterine fibroids were not associated with an increased risk of developing endometrial cancer (http://www.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the total number of women with gynecological diseases was 4537, with 59 (1.30%) diagnosed as EC. To note, the overall incidence rate of women in China is ∼0.063%, which is higher than 0.044% from a previous study on black women in U.S.A. [6]. The 1.30% incidence rate only counts for women with gynecological diseases.…”
Section: Clinical Data Analysis Resultsmentioning
confidence: 63%